ASSESSMENT OF FACTORS INFLUENCING PRODUCTIVE CAPACITIES IN DEVELOPING NATIONS USING MULTI-CRITERIA DECISION ANALYSIS TECHNIQUES - AGHAMAMMADLI, Fuad Pasha oglu (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article presents a comprehensive study of the factors influencing productive capacity in 113 developing countries across the Americas, Asia, and Africa. Using data from the Second Generation of the UNCTAD Manufacturing Capacity Index, the authors analyzed trends from 2018 to 2022 and highlighted eight key determinants shaping productivity at the levels of national economies, business management, and industrial engineering. The research methodology is based on the application of newly developed Multiple Criteria Decision Making (MCDM) techniques. The Interval-Valued Circular Heuristic Fuzzy Analytic Hierarchy Process (AHP) was applied to determine the weights of the criteria, while the Extended AROMAN method was employed to rank the alternatives. The integration of these two innovative approaches not only enhanced the accuracy of the assessment but also contributed new methodological insights to the MCDM literature. The novelty of this study lies in the combined application of two recently developed decision-making methods within one framework, thereby expanding the analytical potential of productive capacity assessment. Considering the scarcity of related studies in existing scholarship, this research significantly enriches the academic discourse. The findings revealed that energy, transportation, and natural capital are the primary drivers of productive capacity, regardless of regional differences. This underlines the global importance of strategic investments in these areas and the urgent need for developing countries to align their policies with these priorities. Beyond methodological innovation, the study provides actionable guidance for policymakers and national governments to design targeted interventions that strengthen productive capacity, particularly through the advancement of energy infrastructure, transport systems, and sustainable resource management.